Hospital clusters of invasive Group B Streptococcal disease: A systematic review. Issue 6 (December 2019) - Collin, Simon M; Lamb, Peter; Jauneikaite, Elita; Le Doare, Kirsty; Creti, Roberta; Berardi, Alberto; Heath, Paul T; Sriskandan, Shiranee; Lamagni, Theresa
Highlights: Group B Streptococcus (GBS) is a leading cause of neonatal sepsis. Hospital outbreaks of invasive GBS are considered to occur infrequently. Transmission of invasive GBS infection in hospitals is poorly understood. Cross-infection between unrelated neonates was reported in 19 hospital clusters. Long intervals between cases may impede the detection of outbreaks. Abstract: Objectives: To characterize outbreaks of invasive Group B Streptococcal (iGBS) disease in hospitals. Methods: Systematic review using electronic databases to identify studies describing iGBS outbreaks/clusters or cross-infection/acquisition in healthcare settings where 'cluster' was defined as ≥2 linked cases. PROSPERO CRD42018096297. Results: Twenty-five references were included describing 30 hospital clusters (26 neonatal, 4 adult) in 11 countries from 1966 to 2019. Cross-infection between unrelated neonates was reported in 19 clusters involving an early-onset (<7 days of life; n  = 3), late-onset (7–90 days; n  = 13) index case or colonized infant ( n  = 3) followed by one or more late-onset cases (median serial interval 9 days (IQR 3–17, range 0–50 days, n  = 45)); linkage was determined by phage typing in 3 clusters, PFGE/MLST/PCR in 8, WGS in 4, non-molecular methods in 4. Postulated routes of transmission in neonatal clusters were via clinical personnel and equipment, particularly during periods of crowding and high patient-to-nurse ratio. Of 4 adult clusters, one was attributed to droplet spread between respiratory cases, one to handling of haemodialysis catheters and two unspecified. Conclusions: Long intervals between cases were identified in most of the clusters, a characteristic which potentially hinders detection of GBS hospital outbreaks without enhanced surveillance supported by genomics.